Research study on seed physical property of Mongolian wheat varieties - Ganzorig, Khishigjargal; Yadamsuren, Myagmarsuren; Tserendorj, Nyamdorj (Proceedings of the Mongolian Academy of Sciences, 2022)
Wheat is the main vital cereal crop in Mongolia (Triticum spp.) The size of the seed is one important feature of seed quality. It is directly related to plant growth, seed yield, market factor and harvest efficiency [1]. Equally important are the size and shape of the seed. The seed in the middle of spike ripens fast, after which the upper and lower parts ripen. Even though seeds in the lower part of the spike fill up at the same time as in the middle section of the spike, the seed ripens later. Seeds in the middle part of the spike have good filling and are bigger in size too. Moreover, they are good plantlets. A two year study was conducted in 2019-2020 to determine the effect of seed size on the yield potential of six wheat varieties, including such early maturing varieties (Darkhan-160, Darkhan-131), medium maturing varieties (Darkhan-34, Darkhan-212) and late maturing (Darkhan-144, Darkhan 181) varieties. Seed samples of 6 varieties were separated in to four groups of seed diameter size, 2.0-2.2 mm, 2.2-2.4 mm, 2.4-2.6 mm, and 2.6-2.8 mm respectively. The seedling density was 350 seeds/m2. The field trial was performed in a completely randomized block design with 3 replications. The 1000 kernel weight in spike parts in tillage stems of varieties, grain yield and seed fraction of the yield were determined by using Grain Scan software. The best qualified seeds were placed at the medium part of the spike. The 1000 kernel weight of the medium part of Darkhan-181, Darkhan-131, and Darkhan-34 varieties reached 40-43 g and Darkhan-144 variety had the highest 1000 kernel weight (40-47 g). The portions of different seed sizes in yield was significant among the varieties planted. The varieties with longer vegetation period result higher portion of larger seeds in yield as compared to varieties with short vegetation period. The portion of large (>2.4mm) seeds in yield increased from 41.6-46.85% to 72.9-76.8% in different maturity varieties (from early to late medium). Grain yield of plots was increased with uniform large seeds in both years. The use of largest seeds resulted in a more competitive cropping system, improving grain yields by 16.9%. The yield decreased by 4.9% by planting seeds (2.0-2.2 mm) smaller than the control fraction (2.2-2.4 mm). The use of uniform large seeds increased both seedling emergence and grain yield. Results demonstrate that medium and mid-large uniform seeds (>2.2mm and >2.4mm) in accordance with the seed properties of the variety were useful in wheat seed production